Digital Transformation in Islamic Education, Improving The Quality of Teachers in Islamic Education in Padangsidimpuan City - Helena, Yanti; Sumanti, Solihah Titin (Institut Agama Islam Negeri (IAIN) Curup, 2024)
Digital transformation in Islamic education has become an important topic in improving the quality of education, including in Padangsidimpuan City. Rapid technological developments have had a significant impact on the way of teaching and learning at various levels of education, including Islamic education. This research aims to analyze how digital transformation can play a role in improving the quality of teachers in Islamic education in Padangsidimpuan City. Using qualitative methods, this research identifies the challenges faced by teachers in implementing technology as well as the strategies implemented to optimize the use of technology in the learning process. The research results show that although there are obstacles in terms of access to technology and teachers' digital skills, with proper training and adequate infrastructure support, digital transformation can have a positive impact on the quality of Islamic education in this area. Therefore, it is important for related parties to continue to improve the quality of training for teachers and expand access to technology in Islamic educational institutions.